2017
DOI: 10.1038/bjc.2017.271
|View full text |Cite
|
Sign up to set email alerts
|

SELECT-3: a phase I study of selumetinib in combination with platinum-doublet chemotherapy for advanced NSCLC in the first-line setting

Abstract: Background:We investigated selumetinib (AZD6244, ARRY-142886), an oral, potent, and highly selective, allosteric MEK1/2 inhibitor, plus platinum-doublet chemotherapy for patients with advanced/metastatic non-small cell lung cancer.Methods:In this Phase I, open-label study (NCT01809210), treatment-naïve patients received selumetinib (50, 75, 100 mg BID PO) plus standard doses of gemcitabine or pemetrexed plus cisplatin or carboplatin. Primary objectives were safety, tolerability, and determination of recommende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…Fifty-five patients were enrolled. Most frequent adverse events (AEs) were fatigue, nausea, diarrhea, and vomiting (Table 3 ) [ 50 ]. Another phase I study evaluated the safety and tolerability of selumetinib as a monotherapy, or in combination with docetaxel as a second-line therapy for Japanese patients with advanced NSCLC.…”
Section: Evidence For Combination Of Chemotherapy and Mek Inhibitors mentioning
confidence: 99%
“…Fifty-five patients were enrolled. Most frequent adverse events (AEs) were fatigue, nausea, diarrhea, and vomiting (Table 3 ) [ 50 ]. Another phase I study evaluated the safety and tolerability of selumetinib as a monotherapy, or in combination with docetaxel as a second-line therapy for Japanese patients with advanced NSCLC.…”
Section: Evidence For Combination Of Chemotherapy and Mek Inhibitors mentioning
confidence: 99%
“…MEKis are in diverse phases of clinical development, including trametinib, which has been approved in combination with the BRAF inhibitor dabrafenib for the treatment of a subset of NSCLC with BRAF V600E mutation (Friday and Adjei, 2008; Greystoke et al, 2017; Planchard et al., 2017; Stinchcombe and Johnson, 2014). However, despite promising co-clinical studies in mouse models and clinical trials (Chen et al, 2012; Greystoke et al, 2017; Planchard et al, 2017), resistance to MEKis is often observed (Soria et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…MEKis are in diverse phases of clinical development, including trametinib, which has been approved in combination with the BRAF inhibitor dabrafenib for the treatment of a subset of NSCLC with BRAF V600E mutation (Friday and Adjei, 2008; Greystoke et al, 2017; Planchard et al., 2017; Stinchcombe and Johnson, 2014). However, despite promising co-clinical studies in mouse models and clinical trials (Chen et al, 2012; Greystoke et al, 2017; Planchard et al, 2017), resistance to MEKis is often observed (Soria et al, 2017). This resistance has been attributed to the heterogeneity of the tumor (Jamal-Hanjani et al, 2017; Swanton and Govindan, 2016) and to intrinsic and acquired resistance from both cancer cells and the tumor microenvironment (Ebert et al, 2016; Manchado et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…An agent that can increase chemotherapy susceptibility in this resistant disease has the potential to substantially prolong patients' lives and enhance cure rates. The combination of MEK inhibition with URML-3881 and cisplatin was well tolerated by animals, mirroring early phase clinical trials in patients that have reported an acceptable side effect profile for combined MEK inhibition and chemotherapy [20], [31].…”
Section: Discussionmentioning
confidence: 57%